Faktor-faktor yang Mempengaruhi Penghidupan Berkelanjutan di Desa Agrowisata - Rahmah, Ulya; Pardani, Cecep (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2025)
This study aimed to analyze the factors influencing sustainable livelihoods in Alamendah Tourism Village, Rancabali District, Bandung Regency, which has rapidly developed through the agritourism sector. A quantitative approach with survey methods was employed, involving 100 respondents selected through probability sampling techniques from a total population of 7,899 households. Primary data were collected through interviews, observations, and questionnaires. Subsequently, data were analyzed using multiple linear regression to determine the effects of age, education, income, natural capital, financial capital, social capital, human capital, and physical capital on sustainable livelihoods. The results showed that simultaneously all independent variables significantly influenced sustainable livelihoods. However, partially, only natural capital, social capital, human capital, and physical capital had a significant positive effect. Meanwhile, the variables of age, education, income, and financial capital showed no significant effect on sustainable livelihoods. This research recommends the importance of increased investment and attention towards natural, social, human, and physical capital as key strategies to support sustainable agritourism development in Alamendah Tourism Village.